Cloning and characterization of O-xylosyltransferase gene from Pinctada fucata martensii. Issue 1 (1st January 2019) - Hao, Ruijuan; Zheng, Zhe; Du, Xiaodong; Jiao, Yu; Deng, Yuewen
ABSTRACT: Glycosaminoglycan (GAG), an important component of proteoglycan (PG), was biosynthesized with the initiation by peptide O-xylosyltransferase. O-xylosyltransferase activity was presented as a marker for increased PG synthesis. In the present study, a novel O-xylosyltransferase (OXT) gene was identified from Pinctada fucata martensii ( PmOXT ). The PmOXT-deduced protein sequence carried a typical water-soluble carbohydrate domain, branch domain, and xylosyltransferase domain. Homologous analysis of PmOXT presented the conserved DXD motif and catalytic structure characteristics. Phylogenetic tree analysis showed the traditional taxonomy and PmOXT clustered with Crassostrea gigas . PmOXT was expressed in all the detected tissues and developmental stages. PmOXT had a significantly higher expression level in the shell formation associated tissues and developmental stages. PmOXT expressed significantly decreased in the central zone of the mantle and marginal zone of the mantle after RNA interference; additionally, OXT activity and GAG content in the extrapallial fluid were significantly reduced compared with the control. Furthermore, the crystal tablets of prismatic layer displayed obvious holes and disordered crystals with obviously rough surface and irregular crystal tablets were observed in the nacre after RNAi. Results suggested that PmOXT affected the shell formation by influencing the formation of GAGs in the process of addition to the core proteins.